One new genus and nineteen new species of ground spiders (Araneae: Gnaphosidae) from Iran, with other taxonomic considerations - Zamani, Alireza; Chatzaki, Maria; Esyunin, Sergei L.; Marusik, Yuri M. (European Journal of Taxonomy, 2021)
One new genus, Zagrotes gen. nov., and 19 new species of ground spiders (Gnaphosidae) are described from Iran: Berinda bifurcata sp. nov. (♂, Bushehr, Khuzestan; southwestern and southern Iran), Berinda hoerwegi sp. nov. (♂♀, Fars, Ilam, Kermanshah, Kurdistan; western and southcentral Iran), Berlandina artaxerxes sp. nov. (♂ Yazd; central Iran), Cryptodrassus iranicus sp. nov. (♂, Kermanshah; western Iran), Drassodes persianus sp. nov. (♀, Kermanshah, Sistan & Baluchistan; western and southeastern Iran), Echemus caspicus sp. nov. (♀, Golestan; northern Iran), Gnaphosa qamsarica sp. nov. (♀, Isfahan; central Iran), Haplodrassus medes sp. nov. (♂, Fars; southcentral Iran), Haplodrassus qashqai sp. nov. (♂♀, Hormozgan, Khuzestan, Lorestan; southwestern to southern Iran), Marinarozelotes achaemenes sp. nov. (♀, Kohgiluyeh & Boyer-Ahmad; southwestern Iran), Marjanus isfahanicus sp. nov. (♀, Isfahan; central Iran), Nomisia ameretatae sp. nov. (♂, Tehran; northern Iran), Prodidomus inexpectatus sp. nov. (♂, Hormozgan; southern Iran), Scotophaeus anahita sp. nov. (♀, Isfahan; central Iran), Scotophaeus elburzensis sp. nov. (♀, Tehran, Zanjan; northwestern and northern Iran), Sosticus montanus sp. nov. (♀, Ilam; western Iran), Synaphosus martinezi sp. nov. (♂♀, Kohgiluyeh & Boyer-Ahmad; southwestern Iran), Zagrotes apophysalis sp. nov. (♂♀, Hormozgan, Kohgiluyeh & Boyer-Ahmad; southwestern to southern Iran) and Zelotes hyrcanus sp. nov. (♀, Mazandaran; northern Iran). These are the first records of the genera Berinda Roewer, 1928, Echemus Simon, 1878 and Marjanus Chatzaki, 2018 in Iran. Additionally, the previously unknown female of Callipelis deserticola Zamani & Marusik, 2017 is described and illustrated, and Berlandina mesopotamica Al-Khazali, 2020 is recorded in Iran for the first time. Furthermore, Berinda idae Lissner, 2016 syn. nov. (Greece, Cyprus) is synonymized with Berinda infumatus (O. Pickard-Cambridge, 1872) comb. nov. (ex. Heser Tuneva, 2004; Greece, Tanzania, Egypt, Israel, introduced to Japan).